2016
DOI: 10.1007/s12008-016-0336-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic and rotor-dynamic interaction for performance evaluation on a Francis turbine

Abstract: Usability is a fundamental quality characteristic for the success of an interactive system. It is a concept that includes a set of metrics and methods in order to obtain easy-to-learn and easy-to-use systems. Usability Evaluation Methods, UEM, are quite diverse; their application depends on variables such as costs, time availability, and human resources. A large number of UEM can be employed to assess interactive software systems, but questions arise when deciding which method and/or combination of methods giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The solid model of impeller and diffuser are shown in Figure 2. on the other hydraulic machines, including Francis turbine [36][37][38], water turbine [39], and tidal turbine [40]. At present, there are relatively few studies on the influence of end clearance on the performance of ESP.…”
Section: Geometry Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid model of impeller and diffuser are shown in Figure 2. on the other hydraulic machines, including Francis turbine [36][37][38], water turbine [39], and tidal turbine [40]. At present, there are relatively few studies on the influence of end clearance on the performance of ESP.…”
Section: Geometry Modelmentioning
confidence: 99%
“…They found that k-ε and k-ω are most suitable for internal flow and performance prediction. Furthermore, as a powerful simulation method, CFD approach was applied on the other hydraulic machines, including Francis turbine [36][37][38], water turbine [39], and tidal turbine [40].…”
Section: Introductionmentioning
confidence: 99%